Psychometric evaluation of a culturally adapted illness perception questionnaire for African Americans with type 2 diabetes - Olayinka O. Shiyanbola; Deepika Rao; Sierra Kuehl; Daniel Bolt; Earlise Ward; Carolyn Brown (BMC, 2022)
Abstract Background Diabetes is burdensome to African Americans, who are twice as likely to be diagnosed, more likely to develop complications and are at a greater risk for death and disability than non-Hispanic whites. Medication adherence interventions are sometimes ineffective for African Americans because their unique illness perceptions are not adequately addressed. The Illness Perception Questionnaire-Revised (IPQ-R) that assesses illness perceptions has shown reliability and validity problems when used with African Americans. Thus, the study objective was to adapt the IPQ-R for African Americans and assess the validity and reliability of the culturally adapted questionnaire. Methods The parent study used an exploratory sequential mixed methods design, to explore African Americans' illness perceptions qualitatively, used the results to adapt the IPQ-R, and tested the culturally adapted IPQ-R items quantitatively. In this paper, a preliminary culturally adapted IPQ-R refined based on the qualitative study, was administered to 170 middle-aged United States-based African Americans with type 2 diabetes in a face-to-face survey. Content, construct, convergent, and predictive validity, including reliability was examined. Pearson and item-total correlations, item analysis, exploratory factor analysis, multiple linear regression analysis, and test-retest were conducted. Results A revised culturally adapted IPQ-R was identified with a 9-factor structure and was distinct from the old factor structure of the original IPQ-R. The 'consequences' domain from the IPQ-R occurred as two factors (external and internal consequences) while the 'emotional representations' domain in the IPQ-R emerged as separate 'present' and 'future' emotional representation factors. Illness coherence' was differently conceptualized as 'illness interpretations' to capture additional culturally adapted items within this domain. Most items had factor loadings greater than 0.4, with moderate factor score correlations. Necessity and concern beliefs in medicines significantly correlated with domains of the culturally adapted IPQ-R. Pearson's correlation values were not greater than 0.7, indicating good convergent validity. The culturally adapted IPQ-R significantly predicted medication adherence. None of the correlation values were higher than 0.7 for the test-retest, indicating moderate reliability. Most domains of the culturally adapted IPQ-R had Cronbach's alpha values higher than 0.7, indicating good internal consistency. Conclusions The results provide preliminary support for the validity of the culturally adapted IPQ-R in African Americans with diabetes, showing good construct, convergent and predictive validity, as well as reliability.